Sunflower storage proteins are transported in dense vesicles that contain proteins homologous to the pumpkin vacuolar sorting receptor PV 72 - Molina, María Isabel (2006)
Storage proteins are transported to a special storage compartments in seeds by Golgi dependent or independent pathways depending on the plant species. The aim of this work was to study the sunflower storage protein transport pathway and identified component of the sorting machinery. Immature sunflower seeds were analyzed by subcellular fractionation (using percoll and sucrose gradients) and electron microscopy. The vesicles isolated with percoll, have precursors of 11S globulins, α-TIP, δ-TIP, BiP, and two proteins that have homology to the pumpkin vacuolar sorting receptor PV72. Sucrose isolated vesicles have the same composition than percoll ones, except for the lack of BiP and the presence of only one protein that has reactivity with pea VSR BP80. Electronic micrographies of developing seeds show that the formation of electron dense aggregates starts in the endoplasmic reticulum, and that these aggregates are very abundant in the trans-Golgi apparatus, where release of dense vesicles happens. These vesicles contain a homolog of PV72 in their membranes. Storage proteins are also detected in multivesicular bodies whose membranes have reactivity with PV72 serum. All these results indicated that sunflower storage proteins are transported to protein storage vacuoles by a Golgi dependent pathway in a process in which homologous of PV72 are involved.